2009
DOI: 10.1016/j.urology.2009.02.066
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Adenosine Triphosphate-stimulated ATP Release Suggest Association Between Cytokine and Purinergic Signaling in Bladder Urothelial Cells

Abstract: Objective To determine whether antiproliferative factor (APF) or epidermal growth factor (EGF) can induce changes in purinergic signaling in normal bladder urothelial cells (BUC) and/or whether antagonizing EGF activity or blocking ATP-purinergic receptors can induce changes in purinergic signaling in interstitial cystitis (IC) cells. Methods IC and normal BUC were obtained from patients’ bladder biopsies. IC BUC were treated with genistein, which antagonizes EGF’s activity, while normal BUC were treated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 18 publications
0
31
1
Order By: Relevance
“…It has been shown previously that bladder uroepithelial cells grown in vitro release ATP in response to stretch and exogenous ATP (29,30,31). These previous studies also reported an increased ATP release from uroepithelial cells from patients The black bars show estimated ATP levels generated by the infected cells and are calculated by subtracting the ATP levels generated by IA2 itself from the measured ATP levels in the coincubation experiments (cells plus IA2 [10 8 CFU/ml]).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…It has been shown previously that bladder uroepithelial cells grown in vitro release ATP in response to stretch and exogenous ATP (29,30,31). These previous studies also reported an increased ATP release from uroepithelial cells from patients The black bars show estimated ATP levels generated by the infected cells and are calculated by subtracting the ATP levels generated by IA2 itself from the measured ATP levels in the coincubation experiments (cells plus IA2 [10 8 CFU/ml]).…”
Section: Discussionmentioning
confidence: 94%
“…In a healthy bladder, release of ATP from uroepithelial cells by stretch and distension mediates the sensation of bladder fullness by activation of P2X 3 receptors on suburothelial sensory nerves (5). Pathophysiological conditions cause enhanced bladder release of ATP as shown in patients diagnosed with interstitial cystitis (29,30,31). Although several studies have shown that pathology often results in augmented ATP release from the urothelium, there have not been any studies of ATP release from urothelium infected with bacteria.…”
mentioning
confidence: 99%
“…The urothelium, once thought to provide an impermeable barrier only, is now suggested to have "neuron-like" properties such as plasticity and sensory, transducive, and signaling capabilities, especially in the context of bladder inflammation (2,5,7,8,(61)(62)(63)(64). Urothelial cells share a number of similarities with sensory neurons, including the expression of receptors such as purinergic, norepinephrine, acetylcholine, neuropeptide-and protease-activated receptors, acid-sensing ion channels, neurotrophin receptors, and transient receptor potential channels (2,5,7,8,(61)(62)(63)(64). Because of functional receptor expression and secretion capabilities, urothelial-mediated communication with the detrusor smooth muscle, suburothelial plexus, and/or interstitial cells has been suggested (2,7).…”
Section: Discussionmentioning
confidence: 99%
“…The P2X3 receptor subunit was upregulated during stretch of cultured urothelial cells from patients with IC [645]; P2X2 and P2X3 receptor expression has been demonstrated on human bladder urothelial cells (as well as on afferent nerve terminals); the expression was greater in cells from IC bladder [63,662]. ATP-stimulated ATP release is augmented in IC bladder urothelial cells compared to healthy urothelial cells [648]. They showed further that ATP-stimulated release of ATP from healthy urothelial cells can be induced by treatment with epidermal growth factor and that P2X3 receptors are increased.…”
Section: Detrusor Overactivitymentioning
confidence: 99%